Persepsi Masyarakat Desa Long Pelban Dan Long Lejuh Terhadap Pembangunan Pembangkit Listrik Tenaga Air Di Kecamatan Peso Kabupaten Bulungan - Syaini Syaini; Masruri Masruri (Journal of Innovation Research and Knowledge, 2026)
This study aims to determine the perceptions of the communities of Long Pelban and Long Lejuh Villages toward the construction of a Hydropower Plant in Peso District, Bulungan Regency, and to identify the factors influencing the development of the Hydropower Plant in Peso District, Bulungan Regency. The research employed a qualitative research method. The data sources were obtained from informants relevant to the research topic. The data used in this study were collected through observation based on field conditions, as well as interviews and documentation. The informants consisted of the governments of Long Pelban and Long Lejuh Villages and the residents of Long Pelban and Long Lejuh Villages, totaling 30 participants. The results revealed that, in the cognitive component, the communities of both villages were aware of and supported the planned development activities. In the affective component, the communities of both villages showed a highly positive response and accepted the development program. In the conative component, the communities of both villages were prepared for future conditions, including relocation activities and adapting to life in new settlement areas. Meanwhile, the supporting factors for the development included supervision and natural resources, whereas the inhibiting factors consisted of land acquisition and transportation access.